Literature Review: Physical Activity Pattern and Depression During the Covid-19 Pandemic in Adolescents - Nina Mustikasari; Handayani Handayani (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
The spread of Covid-19 cases throughout the world, including Indonesia, has caused regional governments to issue regional implementation policies. This directly affects people's behavior, especially in physical activity. Lack of physical activity and limited activities outside the home also cause depression in society. This literature review begins with topic selection, selecting keywords to searching for journal references. The basic data used include Google Schoolar, Sinta and Pubmed. The keywords used are physical activity, the covid-19 pandemic, behavior, adolescents and adults, and depression. This study searches a reference study list that includes 3,060 studies retrieved via search engines. A total of 25 articles were included in and 10 articles were included in the discussion. The results of this study are that the Covid-19 pandemic has changed the pattern of people's activities and the combination of physical activity and social activity causes symptoms of depression in the community.Keywords: Covid-19, Physical Activity, Depression